Remarks on Anatol Rapoport's Paper - Wood, Marshall K. (Management Science, 1961)
Professor Rapoport's article in this issue (Rapoport, A. 1961. Three modes of conflict. Management Sci. 7 (3) 210–218.), and his recent book on the same subject, “Fights, Games and Debates,” provide mush valuable insight into the problems of conflict resolution. I am in agreement with this principles for the resolution of conflicts among individuals, whenever his basic assumptions are applicable. The application of these principles is difficult even in individual debate under favorable circumstances, as is evidenced by the wide discrepancy between Professor Rapoport's precepts and his practice as displayed in his comments on my paper in this issue. These principles are incomparably more difficult to apply in disputes between nations, in which the protagonists are not free agents, but must each answer to a constituency some part of which, at least will criticize his every move. Further, I question the applicability of Professor Rapoport's basic assumptions in the case of the present East-West conflict. Professor Rapoport assumes implicitly that both parties to a conflict wish to resolve it; and he assumes explicitly that both parties have a similar psyche. I do not believe that either of these assumptions is valid as applied to the current conflict between the U.S. and the Soviet Union.